Ministry Of Tourism Decree No. 215 Of The Year 2013 Issued on 6/3/2013 = وزارة السياحة قرار رقم 215 لسنة 2013 صادر بتاريخ 6/3/2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.